Vicinal difunctionalization of carbon–carbon double bond for the platform synthesis of trifluoroalkyl amines - Ferenc Béke (Nature Portfolio, 2020)
Metal-free olefin diamination may display challenges, especially when targeting fluorinated amines. Here, the authors report a double nucleophilic functionalization of an activated alkene originated from a trifluoropropenyliodonium salt with two nucleophiles for the selective synthesis of trifluoromethylated ethylene amines and diamines.